The Influence Of Company Size, Liquidity, Profitability, And Leverage On Islamic Social Report Disclosure - rachman, Dicky; Afendi, Arif; Wahab, Wahab; Rasyidin, Muhammad (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Purpose - Determine the influence of company size, liquidity, profitability and leverage on Islamic Social Reporting (ISR) disclosure in companies listed on the Jakarta Islamic Index (JII) for the 2017-2021 period.Method - This study uses a quantitative approach using secondary data. The research sample was selected through purposive sampling method and obtained 10 companies registered in the Jakarta Islamic index.Result - Return on assets has a negative and non-significant impact on the Islamic banks share price in the stock exchanges, the return on equity and price/earnings ratio have a non-significant positive impact on the banks share price, while there is a negative and significant impact between earnings per Share and the banks share price index.Implication - This research becomes information and assessment for companies listed on the JII because information-rich social responsibility reports show the company's commitment to be accepted.Originality - Research on ISR disclosure is still rarely researched, the use of companies listed on the JII is because previous research mostly discussed Islamic banks, while there are still many companies other than Islamic banks. The JII was chosen as the research object because the stock index on JII meets the criteria for the sharia system in the sharia capital market so that it gets attention for Islamic Social Reporting disclosures.